2016
DOI: 10.1002/hipo.22665
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with β‐adrenergic receptor agonists facilitates induction of LTP and sharp wave ripple complexes in rodent hippocampus

Abstract: Norepinephrine, is involved in the enhancement of learning and memory formation by regulating synaptic mechanisms through its ability to activate pre- and post-synaptic adrenergic receptors. Here we show that β-agonists of norepinephrine facilitate the induction of both associational LTP and sharp wave ripples (SPW-Rs) in acute slices of rat hippocampus in area CA3. Surprisingly, this facilitating effect persists when slices are only pretreated with β-receptor agonists followed by wash out and application of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…This mechanism was proven in an in vitro study in the rodent [25]. This study implies an improvement in memory consolidation via increased hippocampal sharp wave ripples.…”
Section: Concluding Remarks and Implicationsmentioning
confidence: 70%
See 2 more Smart Citations
“…This mechanism was proven in an in vitro study in the rodent [25]. This study implies an improvement in memory consolidation via increased hippocampal sharp wave ripples.…”
Section: Concluding Remarks and Implicationsmentioning
confidence: 70%
“…Mostly, sharp wave ripples arise from the hippocampus' CA3 subregion and originate during sleep or immobility [24]. In vitro experiments in the rat indicated that ß -adrenoreceptor agonism can facilitate sharp wave ripples and LTP [25], supporting the NA's role in modulating sharp wave ripples as well as synaptic plasticity and thereby hippocampal representations to consolidate memory (Figure 1). …”
Section: Memory Encoding and Consolidation Are Promoted By Locus Cmentioning
confidence: 99%
See 1 more Smart Citation
“…If activation of b-ARs was temporally paired with occurrence of SPW-Rs, conditions for generation of b-LTP could be met. NE is released in response to novelty and arousal (Aston-Jones, Rajkowski, Kubiak, & Alexinsky, 1994;Vankov, Herv e-Minvielle, & Sara, 1995), and application of NE suppresses generation of in vitro SPW-Rs via activation of a1-adrenergic receptors (Ul Haq et al, 2016). However, selective activation of b-ARs increases the incidence of SPW-Rs, and this b-AR-dependent SPW-R facilitation is also observed with washout of NE (Ul Haq et al, 2016).…”
Section: B-ars and Hippocampal-cortical Network Oscillationsmentioning
confidence: 99%
“…NE is released in response to novelty and arousal (Aston-Jones, Rajkowski, Kubiak, & Alexinsky, 1994;Vankov, Herv e-Minvielle, & Sara, 1995), and application of NE suppresses generation of in vitro SPW-Rs via activation of a1-adrenergic receptors (Ul Haq et al, 2016). However, selective activation of b-ARs increases the incidence of SPW-Rs, and this b-AR-dependent SPW-R facilitation is also observed with washout of NE (Ul Haq et al, 2016). This NE-mediated sequence of SPW-R suppression followed by enhancement may enable both an immediate, focused, behavioral response and delayed, but increased, opportunities for synaptic plasticity and memory encoding.…”
Section: B-ars and Hippocampal-cortical Network Oscillationsmentioning
confidence: 99%